Stroke in paroxysmal atrial fibrillation: report from the Stockholm Cohort of Atrial Fibrillation - Friberg, Leif; Hammar, Niklas; Rosenqvist, Mårten (European heart journal, 2010)
Aims Knowledge about stroke risk in paroxysmal atrial fibrillation (PxAF) is limited. Although current guideline recommendations advocate the same treatment as in permanent atrial fibrillation (PermAF), most patients with PxAF do not receive prophylactic anticoagulation. The aim of this study is to investigate whether there are differences in stroke risk between PxAF and PermAF. Methods and results All patients with PxAF (n = 855) and PermAF (n = 1126) treated for atrial fibrillation (AF) during 2002 at one of Scandinavia's largest hospitals were followed-up for 3.6 years regarding incidence of stroke. Information about type of AF, comorbidity, medication, and clinical events during follow-up was acquired from medical records and the National Register of Hospital Discharges. The incidence of ischaemic stroke was similar in PxAF and PermAF (26 vs. 29 events/1000 patient years). The multivariable-adjusted hazard ratio (HR) for ischaemic stroke in PxAF compared with PermAF was 1.07 (95% CI 0.71–1.61) in subjects without prior stroke. The corresponding HR for any stroke, ischaemic or haemorrhagic, was 0.89 (95% CI 0.61–1.30). Compared with the general population, ischaemic stroke was twice as common as expected in PxAF after standardization for age and sex (standardized incidence ratio 2.12, 95% CI 1.52–2.71). PxAF patients who took warfarin had approximately half as many ischaemic strokes as those who did not take warfarin (HR 0.44, 95% CI 0.30–0.65). Conclusion Ischaemic stroke is about as common in PxAF as in PermAF, and about twice as common as in the general population. Yet, PxAF patients do not receive protective anticoagulant treatment as often as patients with PermAF do. It is therefore important to increase the use of anticoagulants among PxAF patients in accordance with current guideline recommendations.